2020
DOI: 10.1021/acs.energyfuels.0c02190
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Bush-Like Ru/NiO-Ni Foam Catalyst and Its Performance in Hydrogen Production from Sodium Borohydride Alcoholysis

Abstract: A NiO–Ni foam composite carrier was prepared by the hydrothermal method. Ruthenium metal was supported on the NiO–Ni foam by electroplating, obtaining a highly active bush-like Ru/NiO–Ni foam catalyst. To investigate the effect of NiO on the structure and performance of the catalyst, a Ru/Ni foam catalyst was prepared as a reference. The structures of the carrier and both catalysts were characterized by X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectroscopy, and the performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…04-0850). 30 Notably, due to Cu nanoclusters loaded on NiFe LDH obstructing the exposure of the related surface crystal plane, the intensity of the surface peak at 2 θ = 22.29° was significantly decreased. In addition, considering that the NF substrate might be easily oxidized into Ni-based hydroxide during the hydrothermal reaction, a comparison sample was synthesised via the same method without adding Ni and Fe sources in step 1.…”
Section: Resultsmentioning
confidence: 97%
“…04-0850). 30 Notably, due to Cu nanoclusters loaded on NiFe LDH obstructing the exposure of the related surface crystal plane, the intensity of the surface peak at 2 θ = 22.29° was significantly decreased. In addition, considering that the NF substrate might be easily oxidized into Ni-based hydroxide during the hydrothermal reaction, a comparison sample was synthesised via the same method without adding Ni and Fe sources in step 1.…”
Section: Resultsmentioning
confidence: 97%
“…Then, 30 mL of deionized water was injected through a rubber plug sealed flask by a syringe. The temperature of the reaction solution was carefully controlled by water bath (6,10,15,20,25,30,35,40,45, and 50 °C).…”
Section: Catalytic Hydrogen Evolution Testmentioning
confidence: 99%
“…Hydrogen storage, transportation, and production are critical for hydrogen industrial applications. Sodium borohydride (NaBH 4 ) is a kind of high-density hydrogen storage material with nontoxic, nonflammable, and excellent stability in alkaline solution, which can generate high-quality hydrogen with the presence of suitable catalysts. Highly efficient catalysts are critical to the application of hydrogen generation from catalytic hydrolysis of NaBH 4 solution. , A variety of catalysts including noble metals (e.g., Ru and Pt) and transition metals (e.g., Co and Ni) have been widely studied. Among these catalysts, inexpensive Co-based materials with high reactivity may be the most promising candidate. , However, few active sites, difficult recovery, lower surface area, and particle agglomeration impede its application. , …”
Section: Introductionmentioning
confidence: 99%
“…For a long time, borohydrides have been used as reducing agents in chemical synthesis and solid rocket fuel . With further research, it was found that borohydrides are also a good hydrogen carrier and ionic conductor, and they have been widely used for solid state hydrogen storage, hydrolysis, alcoholysis, and pyrolysis for hydrogen production, fuel cells and several other fields. For example, Xu et al recently found that doping perovskite solar cells (PSCs) materials with borohydrides can significantly improve their photoelectric conversion efficiency and stability. In addition, some researchers , have found that borohydrides can participate directly in the fuel cell reaction, which makes hydrogen fuel cell vehicles safer and more reliable because it avoids the hydrogen storage step.…”
Section: Introductionmentioning
confidence: 99%